PERAN DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN BOGOR DALAM PENGEMBANGAN EKOWISATA DI KABUPATEN BOGOR - Tri Rahayuningsih; E.K.S Harini Muntasib (Media Konservasi, 2012)
Bogor district have a good potential of ecotourism, but recently only a few sites were developed and known by community. One of the keys to success is active participation of the stakeholders involved, particularly the Culture and Tourism Agency (CTA) of Bogor District, in introducing and offering the existing ecotourism potential.  This research was conducted to identify the role of CTA of Bogor District in the development of ecotourism in Bogor.  Data on action taken and policy issued by the CTA were collected through participative observation and in-depth interview using interview guidance.  The result showed that the Agency had actively participated in the ecotourism development of Bogor District, and built cooperation or partnership with various stakeholders.  However, the Agency’s policy should be synchronized with the policy of other stakeholder in the ecotourism development of Bogor District.   Keyword: Department of Culture and Tourism - Bogor district, Role, Development, Ecotourism.